Measuring the Role of Satisfaction in Website Usability Model - Nur Sukinah, Aziz; Adzhar, Kamaludin; Noor Suhana, Sulaiman; Azliza, Yacob (American Scientific Publisher, 2018)
Usability is about making website as user-friendly as possible. There are many elements for website usability such as learnability, navigation, interface, efficiency and much more. Most of the previous researches list the elements of website usability and the model for website usability in hierarchical models. Therefore, it makes the model of website usability become complex because it consists many elements. This paper explores existing studies on website usability model to identify the elements for website usability model from previous studies. In the study, the website usability construct are analysed as second order construct. Many studies have proposed website usability models that include the satisfaction. Thus, this study also validates the website usability model and analysis the mediating roles of satisfaction in the relationship between website usability and intention to use. The study identified effectiveness, efficiency, learnability, navigation, content, interface design and accessibility as elements